2007
DOI: 10.1159/000108319
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetics of IGH rearrangements in non-Hodgkin B-cell lymphoma

Abstract: Rearrangements involving the IGH gene have been identified in about 50% of non-Hodgkin B-cell lymphomas (NHLs) and correlated to clinically relevant subgroups. However, the detection rate largely varied with the technique used. We analyzed the incidence of IGH rearrangements using several fluorescence in situ hybridization (FISH) techniques on metaphases obtained from 96 patients with nodal NHL. An IGH rearrangement was identified in 71 cases (74%). A t(14;18)(q32;q21) was found in 37 of the 42 follicular lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 118 publications
1
8
2
Order By: Relevance
“…It should be noted that we found IGH translocations in 70% of the patients with small‐bowel DLBCL. This incidence is much higher than that observed in previous studies, in which the incidence has been reported to be 25–53% in DLBCLs . Our incidence of IGH translocations in small‐bowel DLBCL was also higher than that seen in cases of gastric DLBCL in our previous study (32%) .…”
Section: Discussioncontrasting
confidence: 68%
“…It should be noted that we found IGH translocations in 70% of the patients with small‐bowel DLBCL. This incidence is much higher than that observed in previous studies, in which the incidence has been reported to be 25–53% in DLBCLs . Our incidence of IGH translocations in small‐bowel DLBCL was also higher than that seen in cases of gastric DLBCL in our previous study (32%) .…”
Section: Discussioncontrasting
confidence: 68%
“…In contrast, similar data on MYC/BCL6 DHL is limited: case reports and a few case-series are available in the literature totalling approximately 40 cases. 18,[22][23][24][31][32][33][34][35] BCL6 is a transcriptional repressor, whereas BCL2 is an inhibitor of apoptosis. As BCL2 and BCL6 have different functions, it seems reasonable to hypothesize that patients with MYC/ BCL6 DHL may have clinicopathological features that differ from MYC/BCL2 DHL patients.…”
Section: Discussionmentioning
confidence: 99%
“…The t(8;14)(q24;q32) translocation has been found in 5–15% of DLBCL cases , but we found this translocation in only 4.3% of DLBCL cases. Recurrent translocations involving IGH were also found in other studies . In our study, t(3;14)(q27;q32)(12.2%) was the most frequently observed translocation mutation according to cytogenetic analysis, which suggested that IGH (14q32) was the most frequent translocation with BCL6 (3q27).…”
Section: Discussionmentioning
confidence: 99%